2021
DOI: 10.1186/s12951-021-00836-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimally biosynthesized, PEGylated gold nanoparticles functionalized with quercetin and camptothecin enhance potential anti-inflammatory, anti-cancer and anti-angiogenic activities

Abstract: Background The development of nano delivery systems is rapidly emerging area of nanotechnology applications where nanomaterials (NMs) are employed to deliver therapeutic agents to specific site in a controlled manner. To accomplish this, green synthesis of NMs is widely explored as an eco-friendly method for the development of smart drug delivery system. In the recent times, use of green synthesized NMs, especially metallic NMs have fascinated the scientific community as they are excellent carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Three compounds such as quercetin, kaempferol and isorhamnetin are highly connected with their supposed targets and can be thought as effective compounds in hawthorn leaves. As a naturally occurring polyphenol, quercetin was reported to possess antioxidant, anti-inflammatory, and antiallergic activity ( 29 , 30 ). Kaempferol, which belongs to the family of flavonoids, is a secondary plant metabolite with a hydroxyl phenylchromenone structure ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three compounds such as quercetin, kaempferol and isorhamnetin are highly connected with their supposed targets and can be thought as effective compounds in hawthorn leaves. As a naturally occurring polyphenol, quercetin was reported to possess antioxidant, anti-inflammatory, and antiallergic activity ( 29 , 30 ). Kaempferol, which belongs to the family of flavonoids, is a secondary plant metabolite with a hydroxyl phenylchromenone structure ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesized GNPs were capped using polyethylene glycol 9000 (PG9) before the functionalization with quercetin as an anticancer drug model. The MTT results against MCF-7 showed that only the biosynthesized GNPs functionalized with PG9 and quercetin induced cell death, whereas quercetin alone and the green GNPs without PG9 or quercetin did not show significant antiproliferative activity [56].…”
Section: Plant Extracts-based Nanocarriersmentioning
confidence: 95%
“…To advance the employment of these nanocarriers, surface modication agents should be substituted, including polyethylene glycol (PEG), leading to PEG-conjugated nanocarriers or surface-covered MSNs. 60 As a temporary biomolecule found in nature, messenger RNA (mRNA) facilitates the translation of genetic information from genes encoded in DNA to proteins dispersed throughout the cell. 61 Fortunately, several carriers, and biomaterials developed for DNA and small interfering RNA (siRNA) have shown signs of hopeful development as a basis for mRNA delivery methods.…”
Section: Overviewmentioning
confidence: 99%